Social Impacts Of Applying Legal Pluralism In Muslim Majority Countries - Adil Muhammed Padaliyil (Al-Fadlan: Journal of Islamic Education and Teaching, 2025)
A legal system can be defined as a set of rules and procedures that a community usesto interpret and enforce its laws, which is compulsory for the well-being of every socialinstitution. When there is existence of multiple legal systems within one society orgeographical territory, it can be called as Legal pluralism. As countries like India has specialIslamic laws and principle for those who follow Islam. And other communities’ issues will bedealt by secular courts. As if a Muslim dies, his properties can be divided for his ancestorsaccording to Islamic law, or can be divided equally according to public legal system. Thesystem is favorable and also hate-provoking at the same time in a social perspective. Mystudy concentrate on those social responses to the system. The system doesn’t shrink only inIslamic law, but also in other religious laws like Hindu Marriage Act, 1955. But Islam is oneand only religion flourished by a legal system that deals with all the deeds of a human. So,the topic is more likely to concentrate the Islam. We can get the relevance of topic frominvolvement of even Muslim minority countries like USA, Canada, Australia and Germany inconducting debates on allowing legal pluralism. The paper also concentrate especially onMuslim-majority countries such as Indonesia and Egypt. The research can give an idea onhow much applicable and practicable is legal pluralism.